MEMBANGUN PENGETAHUAN LINGKUNGAN SEJAK DINI: STUDI PENGGUNAAN EDUCATION CARD DI UPT SPF SD NEGERI PAMPANG - Ayu, Sri Wahyuni; Suryani Sahabuddin, Erma; Faisal, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low level of environmental literacy among elementary school students. This study aims to determine (1) the description of the use of Education cards at the Pampang State Elementary School UPT SPF, (2) the description of students' environmental literacy skills at the Pampang State Elementary School UPT SPF, and (3) the effect of using Education cards on students' environmental literacy skills at the Pampang State Elementary School UPT SPF. This study uses a quantitative approach with an experimental method and a quasi-experimental design of the Nonequivalent Control Group Design type. The research population included all students at UPT SPF SD Negeri Pampang, while the sample was determined using purposive sampling, namely class V(A) as the control class and class V(B) as the experimental class, each consisting of 30 students. Data collection was carried out through observation and tests, while data analysis used descriptive and inferential statistics. The results of this study indicate that there is a significant effect of the use of Education cards on students' environmental literacy skills.